REGULATORY EVOLUTION OF THE INCOME TAX ADVANCE IN ECUADOR - Gutiérrez Jaramillo, Néstor Daniel (2016)
The present work is detailed analysis of the most relevant aspects related to the normative evolution of the Income Tax Advance for taxpayers who are obliged to keep accounts from 2008 to the present date. Configuration aspects such as calculation conditions, forms of payment, right to return and exemption or reduction of payment are valued. The reason for the study is because the relevance of its application is still, at present, an element of discussion, since it is still considered as confiscatory and illegitimate.The objective was to carry out a normative analysis of the evolution in the form of calculation, payment and general benefits in the Advance from the year 2008 to October of 2016. Applying the methodology of documentary analysis based on the current legal tax legislation we took as its main element The Internal Tax Regime Law and its Regulations.Likewise, the sentence of the Constitutional Court that declares the legality of the Anticipation, as well as other investigations related to the subject, are taken as the theoretical basis.As a result, since 2016, the Advance takes the approach of Minimum Income Tax, with no right to refund or later compensation. And in 2016 the legal possibility for the return of a part of the canceled value is given.